Strikes and eventful identities: South Africa’s public sector strikes, 2007 and 2010 - Ceruti, Claire Helen Mary (University of the Witwatersrand, Johannesburg, 2023)
This is a study of rupture and its deflection in public striker identities over two politically charged strikes in 2007 and 2010. The thesis reconstructs each strike as a series of possibilities, taking a dynamic and temporal view attuned to the development of contradictions in a way sensitive to what else might realistically have developed out of these given ‘moments’ or conjunctures of forces. The data was gathered longitudinally in each strike and across the two strikes, which were three years apart, via interviews, observation and analysis of toyi-toyis and particularly photos, which were used to track slogans and their development. The thesis uncovers eventful identities beneath the rehabilitation or reconstitution, twice, of the strained Tripartite Alliance amongst the ruling party, the ANC, the main trade union federation (Cosatu) and the South African Communist Party; it also uncovers peculiarly relational classed imagery suggestive of exploitation even in simple strike-ready identities, entwining and subtly altering people’s more common everyday consumption-based models of class. The thesis traces strikers’ identities against the histories of each strike to find identities in punctuated dialogue with larger forces, thereby restoring the role of this kind of contradiction in processes of identity destabilisation as well as in eventfulness. The thesis finds that strikers’ identities were deformed in relation to the alliance by successive shocks over the course of the two strikes. The strikes did not rupture, but did puncture, the practice of the alliance. Despite a variety of deflections, faint reinterpellations percolated through these experiences. In the first strike, in 2007, the shock to identification with government, experienced by the strikers as well as the union officials, intensified as the strike continued and drove one aspect of a ‘power flip’ which I noted in the development of strikers’ discourse over the strike in a shift from entreating government, to asserting mutual dependence, to reversing the dependency - wanting to turn on its head the actually existing practice of the alliance by demanding a government that listens to workers – and at the same time conceiving the centrality of the strikers’ own work in relation to these powers. At the end of the first strike, the shock to identities with government was truncated by pragmatism and diverted and to the political kingdom, in the person of Zuma. But that deflection built up expectation for the restored alliance, and the second strike burst forth from disappointed expectations (a second shock to identities with government) to put Zuma to the test. This strike expressed mainly the political dimension of the power flip. The end of the strike incurred a third shock: a divergence in the strategic views of union officials from those of strikers, which occurred partly because the union leaders who had re-established loyalties and, they believed, influence within the alliance (partly because of the first strike). The de-identifications towards the end of this strike were deflected in more complicated ways. Although it appeared from a distance that the alliance had worked again to let off steam and iron over damage, that view overlooked how strikers’ identifications had taken damage in the double test of the ANC; at least some were in a liminal state I call identity damage, not having re-identified themselves but forced to imagine life outside the ANC. So the thesis overall illustrates the development of these eventful identities, which may survive the failure of an event to develop (a near event). The thesis thus, first, returns contradiction (and agency) to the study of eventfulness (rupture), as well as, through a finer view of deflection, examining why eventfulness often fails to develop; second, it foregrounds subjectivity in contradictory circumstances to stretch studies of classed identities and identity processes into an under-examined arena (strikes); and thereby, third, it adds an under-examined dimension -strikers’ subjectivities - to study of the cohesion/disintegration of the alliance and the unravelling of ANC hegemony to show that the alliance’s mechanisms of maintenance were also ‘storing up’ contradiction and damage to its future integrity. The concepts of misidentification and identity damage were developed to present identity processes in contradictory situations as punctuated and to refine understanding of rupture at the subjective level.
A thesis completed in fulfilment of the requirements of the degree of PhD, Department of Sociology, at the Faculty of the Humanities, School of Social Sciences, University of the Witwatersrand, Johannesburg, in 2023.
Keywords: Strikes; Identity; Events; Eventfulness; Identity Events; Tripartite Alliance; Cosatu; Anc; SACP; Two-Stagism; Classed Identity; Strike Identities; Identity Damage; Misidentification; UCTD; SDG-16: Peace, justice and strong institutions